The Oxford handbook of autism and co-occurring psychiatric conditions - White, Susan Williams; Maddox, Brenna B; Mazefsky, Carla A (New York : Oxford University Press, 2020)
'People with autism spectrum disorder (ASD) are often diagnosed, and treated for, co-occurring mental health disorders. Co-occurring problems are, in fact, a primary reason for referral and treatment-seeking. Research on comorbidity and its management in youth and adults with ASD has expanded at a rapid rate over the last decade. This is the first comprehensive volume on the topic of co-occurring psychiatric conditions and symptoms in ASD. In this Handbook, internationally recognized clinical scientists synthesize the research on assessment and evidence-based treatment for a broad range of conditions as they present in ASD, from childhood through adulthood. In addition to coverage of formal diagnoses that frequently present in ASD (e.g., mood and anxiety disorders), common behavioural concerns (e.g., psychosexual and sleep problems) are also addressed. Each chapter summarizes the condition or disorder as it presents in ASD, and presents the extant research on its prevalence, developmental course, etiology, and assessment and diagnosis in the context of ASD. Each chapter also includes a summary of evidence-based treatment approaches or current best practices for intervention, as well as a case example to demonstrate application. Chapters are also included to synthesize broader issues related to co-occurring psychiatric conditions in ASD, including a historical overview and conceptual framework for co-occurring conditions in ASD, crisis management, and psychopharmacology. In sum, this handbook is comprehensive compilation of the current evidence-base and recommendations for future research to inform clinical practice related to co-occurring psychiatric conditions and symptoms in ASD'--
Keywords: Autism -- Handbooks, manuals, etc; Anxiety disorders -- Handbooks, manuals, etc